Enhance Eco-Handloom Product Performance: Entrepreneurial Orientation and Pro Competition Absorptive Capacity - Liharman Saragih; Romindo M Pasaribu (Ilomata International Journal of Management, 2026)
In the Lake Toba region, a lot of weavers attempt to make eco-handloom items like ulos.  However, in order to compete, they must improve their ability to absorb in order to make eco-handloom. In this regard, we aimed to assess the Product Performance using partial least squares structural equation modeling (PLS-SEM) in 242 weavers on the coast of Lake Toba in Indonesia. The impact of Entrepreneurial Orientation on Product Performance, with Pro Competition Absorptive Capacity as a moderator investigated in this study.  According to the study's findings, eco-handloom weavers must have an entrepreneurial mindset in order to improve the performance of their products. The results shows that Entrepreneur Orientation effects on Product Performance is positive and significant. The moderating effects of Pro Competition Absorptive Capacity on the relationship between Entrepreneurial Orientation and Product Performance is positive and significant. Businesses that adopt an entrepreneurial attitude are more equipped to innovate, adapt, and prosper in cutthroat marketplaces.  According to the facts, integrating various viewpoints improves the weaver capacities and promotes long-term success.